Pendampingan Pembuatan Data Statistik Menggunakan Aplikasi SPSS Panitia Pilkades Desa Sukorejo - Qohar, Moh. Abdul; A, Komarudin; Mansur, Ali; Putri , Armia Zulia; Istiqomah, Istiqomah (Santri : Journal of Student Engagement, 2024)
This article aims to describe the process and results of community service activities that seek to increase the knowledge and skills of Tadris Mathematics Uimsya students and the Sukorejo Village head election committee in processing statistical data with SPSS software. Service activities are carried out for 1 (one) month. The stages in service include observation, planning, implementation and evaluation. This service activity was proven to produce statistical data for an average of 1115 people, a median of 1204 people, while the standard deviation was 755,938. From the results of the standard deviation analysis, it was concluded that there was a lack of significant competition between candidates as evidenced by the large standard deviation produced. From the implementation of this service, it is known that the service went smoothly as planned. However, several things still need to be designed better in carrying out similar activities, including the techniques and methods used in the mentoring process.